Bordervoicing - Jukić-Gregurić, Tatjana (Array, 1997)
The need to theorize about theory rarely stems from what anthropologists would call a "lived experience". The problem, however, arises when a hypothetical author starts questioning not telling, narartion, or representation, but the very pledge of transcendence: what happens in those rather narrow strips of time-and-place when the lived experience becomes a threat to the prison-walls of the encyclopedia and suddenly proves more powerful than any system of signification? In such a situation the communicational pact that I have described as borderly produces a disinterested scientific discourse only as a side-effect of its overall discursive activity. What prevails, even in (meta)theory, are texts attempting to bridge the nonetheless unbridgeable gap between signification and reality. Speakers adhering to the orderly communicational pact might indeed see this as an exotic and (quite literally) eccentric occurrence, but speakers ruled by a rapidly and radically shifting cultural and political dominant, having no paradigm to abide by, can rely only on a personalized discourse, on a freshly founded and therefore highly fragile communal consensus.